PENGARUH ATRIBUT SUPERMARKET TERHADAP MOTIF BELANJA DAN DAMAKNYA TERHADA LOYALITAS PELANGGAN DI PAMELLA 1 YOGYAKARTA - Suma Tri Wahyuni (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this research is to describe (1) the influence of supermarket attribute on the hedonicshopping motive in Pamella I Yogyakarta, (2) the influence of supermarket attribute on the utilitarianspending motive in Pamella I Yogyakarta; (3) the influence of supermarket attribute on customer loyalty inPamella I Yogyakarta, (4) the influence of hedonic shopping motive on customer loyalty in Pamella IYogyakarta, (5) influence of utilitarian spending motive to customer loyalty in Pamella I Yogyakarta. Thisresearch is a quantitative research by using media questionnaires distributed to 100 shoppers in Pamella IYogyakarta.The result of the research shows that (1) the supermarket attribute has a significant positive effect onhedonic shopping motive in Pamella I Yogyakarta, (2) supermarket attribute has no significant positiveeffect on utilitarian spending motive in Pamella I Yogyakarta, (3) supermarket attribute has significantpositive effect on customer loyalty In Pamella I Yogyakarta, (4) hedonic shopping motive has a significantpositive effect on customer loyalty in Pamella I Yogyakarta, (5) utilitarian spending motive has nosignificant positive effect on customer loyalty in Pamella I Yogyakarta.